Adopting a helicopter-perspective towards motivating and demotivating coaching: A circumplex approach. (January 2019) - Delrue, Jochen; Reynders, Bart; Broek, Gert Vande; Aelterman, Nathalie; De Backer, Maarten; Decroos, Steven; De Muynck, Gert-Jan; Fontaine, Johnny; Fransen, Katrien; van Puyenbroeck, Stef; Haerens, Leen; Vansteenkiste, Maarten
Abstract: Based on Self-Determination Theory, the present study adopts a helicopter-perspective towards motivating (i.e., autonomy support, structure) and demotivating coaching (i.e., control, chaos). Among five independent samples, consisting of individual and team sport coaches ( N  = 893; M age = 37.83 years) and athletes ( N  = 377; M age = 17.46 years), Multidimensional Scaling (MDS) analyses were used to examine how a variety of coaching practices reflective of four different coaching styles (i.e., autonomy support, control, structure, and chaos), assessed with a new vignette-based instrument, related to one another. Findings revealed that the (de)motivating practices could be graphically presented within a two-dimensional circumplex, with the horizontal axis representing the level of need-supportive coaching behavior and the vertical axis representing the level of coach directiveness. Moreover, the four coaching styles could be segmented in eight more specific approaches (i.e. clarifying, guiding, attuning, participative, awaiting, abandoning, domineering, and demanding), which formed an ordered sinusoid pattern of correlations, both among each other and in relation to a variety of critical outcomes (e.g. coach need satisfaction, athletes' motivation). It is discussed how a circumplex approach produces both a more integrative and more fine-grained insight regarding (de)motivating coaching behavior, with resulting implications for practice. Highlights: A new integrative measure of motivating and demotivating coaching. A circumplex pattern of eight coach approaches containing a variety of coaching practices. The gradual approach provides a fine-grained understanding of need-supportive and need-thwarting coaching behaviors. The eight coach approaches relate logically to concurrent measures and both coaches' and athletes' outcomes.